Deglacial Thinning of the Laurentide Ice Sheet in the Adirondack Mountains, New York, USA, Revealed by 36Cl Exposure Dating. Issue 6 (18th June 2019) - Barth, Aaron M.; Marcott, Shaun A.; Licciardi, Joseph M.; Shakun, Jeremy D.
Abstract: Future changes in sea level will largely be dictated by changes in the world's ice sheets. Yet the magnitude and rate at which these ice sheets will respond to climate change remain uncertain, necessitating a deeper investigation into past ice sheet‐climate interactions. Numerous studies have documented the timing and pattern of Laurentide Ice Sheet margin retreat since the Last Glacial Maximum, but few studies have provided vertical constraints necessary for accurate sea level contribution estimates. Here we present 21 36 Cl ages from boulder and bedrock samples along vertical transects spanning 1, 000 m of relief from multiple peaks in the Adirondack Mountains of northeastern New York, USA. Our exposure ages span the Last Glacial Maximum through the last deglaciation, with the highest‐elevation sites ( 1, 500 m) ranging between 25 and 19 ka, and the lower elevation sites (≤1, 300 m) between 16 and 13 ka. These data suggest gradual ice sheet thinning of 200 m initiated at 20 ka followed by more rapid surface lowering of 1, 000 m approximately coincident with Bølling‐Allerød warming. Key Points: The 36 Cl exposure ages from the Adirondacks show regional ice sheet thinning histories The Laurentide Ice Sheet experienced two‐phase thinning in this region 21–14 ka Gradual thinning was followed by rapid retreat coincident with the Bølling‐Allerød